Causes and Mitigation Schemes of Project Delays among Selected Construction Companies in Cebu City - Dela Cruz, Roselyn D.; Polinar, Mark Anthony N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
A project's completion is crucial because it shows that goals and objectives have been met, guarantees client happiness, upholds a project's good reputation, and creates new prospects for those working in the construction business. However, in the field, construction projects need help with their timely execution and successful execution due to project delays, which can also affect costs, schedules, and stakeholder satisfaction. Hence, this phenomenological study explores the lived experiences of the project engineers who have existing projects on what are the perceived factors that cause project delays. On top of that, the study forms a series of recommendations to mitigate the identified causes of project delays. Eight (8) key informants were chosen using purposive sampling to be interviewed individually. In using Colaizzi's approach, eight themes materialized in the study: (1) Poor Management, (2) Limited Manpower, (3) Unskilled Workers, (4) Unforeseen Circumstances, (5) Poor Communication, (6) Financial Capabilities, (7) Insufficient Resources, and (8) External Factors. Ultimately, the authors concluded the need for solid project management practices, proactive risk reduction, and efficient communication to reduce delays and guarantee good project outcomes. Also, the authors concluded that if the entities appropriately and situationally consider these mechanisms recommended in the study, they will result in more precise and targeted responses to project delay issues, leading to service excellence and customer satisfaction.